2005
DOI: 10.1097/01.mlg.0000150417.51835.4f
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal Climate in Laryngectomees after Use of a Heat and Moisture Exchanger

Abstract: The results indicate that short-term use of the HME Prim-Air system rapidly changes the tracheal climate. The significant increase in tracheal temperature and humidity may have beneficial effects on tracheal dryness in laryngectomized patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 10 publications
2
28
1
Order By: Relevance
“…In such measurements extreme care is required to avoid loss of water vapor due to condensation in the sampling tube. 12,13 No commercial equipment is available for these challenging measurements, and experience has shown that custom-built equipment is difficult to develop and maintain. 12,13 Moreover, only a minority of available HMEs thus far have been analyzed both in vitro and in vivo.…”
Section: See the Related Editorial On Page 1559mentioning
confidence: 99%
See 2 more Smart Citations
“…In such measurements extreme care is required to avoid loss of water vapor due to condensation in the sampling tube. 12,13 No commercial equipment is available for these challenging measurements, and experience has shown that custom-built equipment is difficult to develop and maintain. 12,13 Moreover, only a minority of available HMEs thus far have been analyzed both in vitro and in vivo.…”
Section: See the Related Editorial On Page 1559mentioning
confidence: 99%
“…12,13 No commercial equipment is available for these challenging measurements, and experience has shown that custom-built equipment is difficult to develop and maintain. 12,13 Moreover, only a minority of available HMEs thus far have been analyzed both in vitro and in vivo. [12][13][14][15] Therefore, an easy method for assessing HME performance using commercially available equipment could be very useful for medical professionals.…”
Section: See the Related Editorial On Page 1559mentioning
confidence: 99%
See 1 more Smart Citation
“…The functional core material traps and releases a small amount of water during exhalation and inhalation, respectively. With different types of HMEs currently available, the literature is growing rapidly on the effect of HMEs on clinical complaints, 4-9 influence on respiratory function, 2,[10][11][12] in vivo humidity measurements, [13][14][15] and comparison of in vitro measurements. 16,17 However, no comparative data have been published as yet on the performance of the whole range of HMEs available for laryngectomized patients today.…”
Section: Introductionmentioning
confidence: 99%
“…Because of evaporative cooling there is even a slight but important decrease in end-inspiratory temperature with the Provox Normal and the Provox HiFlow (Atos Medical, Hö rby, Sweden) (Ϫ1.5°C and Ϫ1.0°C, respectively). [14][15][16][17] Breathing resistance plays a more profound role in HMEs for laryngectomees than in anesthesiology HMEs. The breathing resistance of a laryngectomee HME should be comfortable, to promote adherence to therapy.…”
Section: Introductionmentioning
confidence: 99%